Waldenström Macroglobulinemia in Hepatitis C: Case Report and Review of the Current Literature - Ryan Nipp; Aaron Mitchell; Allyson Pishko; Ara Metjian (Case Reports in Oncological Medicine)
Background. Recent literature has associated hepatitis C virus with the development of non-Hodgkin lymphoma. Hepatitis C virus infection appears to promote lymphoproliferation, providing a plausible mechanism for a causative association; however, despite prior reports of patients with comorbid hepatitis C infection and Waldenström macroglobulinemia, the literature is in disagreement regarding whether there exists an association between these two conditions. Case Presentation. This case report describes a 57-year-old African-American male with chronic hepatitis C infection and cryoglobulinemia who presented with several episodes of transient confusion and paralysis and was found to have symptomatic hyperviscosity. The recognition of his condition was facilitated by characteristic findings on ophthalmologic examination. He was subsequently diagnosed with Waldenström macroglobulinemia on bone marrow biopsy. Conclusions. An up to date, comprehensive review of the literature suggests an association between hepatitis C and Waldenström macroglobulinemia. Data on optimal treatment of patients with comorbid hepatitis C infection and Waldenström macroglobulinemia is limited. We have provided a comprehensive review of previously explored treatment options to guide management of other similar patients. Our patient has since been treated with repeated plasmapheresis with a plan to pursue antiviral therapy.